Al-sunnah al-fi'liyyah: meaning, method, and validity - Rabie Ibrahim Mohamed Hassan,; Abdul Ghani Md Din,; A’bir Abdul Ghani, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Scholars have different opinions regarding the guidance of the Prophet SAW in determining the law. Does what the Prophet SAW did show that it is obligatory? Or does it show circumcision? Or showing should? So this study was studied to explain the parts of the Prophet SAW's actions and the guidance of each part. The importance of this research is to meet the needs of the people of the Prophet SAW to understand the guidance of the Prophet SAW's actions, and to distinguish between his actions. This study aims to explain the true al-fi'liyyah (or practical) sunnah, along with evidence. And this study will answer the questions, namely: Can sunnah fi'liyyah be used as evidence? And what are the arguments? Are the actions of the Prophet SAW at the same level in the proofs? The researcher will use the inductive method; This is done by studying and exploring the actions of the Prophet SAW, then the researcher uses an analytical and deductive approach in explaining the arguments of each part of the action. Among the results that will be achieved in this study: The actions of the Prophet SAW are abstract and every action done by the Prophet SAW cannot be evaluated and made as an obligatory law, or circumcision, and may God grant success and help.